Pelatihan Membaca Teks Bahasa Inggris Bagi Pegawai Di DPRD Kota Bengkulu - Sari, Ririn Novita; Putra, Dhanu Ario; Rullyanti, Merry; Sumantri, Ajis (Jurnal Gotong Royong, 2024)
Based on Law Number 17 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council and the Regional People's Representative Council and which has been passed down by the Regulation of the Bengkulu City Regional People's Representative Council, it states that the DPRD consists of Members of Political Parties participating in the General Election. elected based on the results of the General Election, and the DPRD is a regional people's representative institution whose position is as an element of regional government administration. Even though the City DPRD rarely uses English in carrying out its activities, they hope to be able to speak English fluently so that if one day they visit abroad or are visited by guests from other countries, they can speak fluently. Through this KKN activity, one of the main programs is training the ability to read English texts to employees at the Bengkulu City DPRD with the aim of ensuring that they are able to at least read English texts fluently. The method for carrying out this activity is Lecture and Practice. The result of this activity is that employees have begun to be able to read English texts well and correctly.